A formação permanente dos professores de educação física no contexto da política educacional do Município de Suzano-SP - Silva, Wellington Dantas da (2014)
Given the number of counties that recently started to enter the Physical Education curriculum in the early years of elementary school and the importance of ongoing training for the professional development of teachers of this subject, we sought through this study highlight the contributions and limitations arising from the ongoing formation process developed in the city of Suzano-SP, during the 2011-2012 biennium, according to the physical education teachers who worked in municipal schools. During this period, the City Department of Education, considering the structural principles of his educational policy, developed a specific process of ongoing training for physical education teachers, emphasizing the involvement and participation of teachers in the organization of training activities. Thus, based on a qualitative research approach, performed a descriptive study of the survey type in order to achieve the proposed through an analysis of the interpretations of the study subjects in relation to the training model offered by the city of Suzano goal. The data collection instruments used for this task were a questionnaire with open and closed questions and a semistructured interview. Results point out limitations in the development of the educational process, such as: a still remarkable dependence on an expert to legitimize the training offered. Moreover, the exchange of ideas and experiences among stakeholders was viewed positively, bringing teachers of the problems faced by network and own fellow professionals